A rhetorical storm: linguistic analysis of uncertainty in severe weather communication - Rosen, Zoey, author; Long, Marilee, advisor; Demuth, Julie, committee member; Schumacher, Russ, committee member (Colorado State University. Libraries, 2019)
Weather forecasts are a product with inherent uncertainty and a wide audience (Compton, 2018). Known as an example of prediction rhetoric (Morss, Demuth, & Lazo, 2008), weather forecasts have been found to be influenced by linguistic and cultural factors in case studies (Pennesi, 2007). However, forecasts are still rarely studied as articles of rhetoric (Compton, 2018). This study analyzed patterns amongst the linguistics of uncertainty expressions in Twitter forecasts during a cluster of tornadoes in March 2018 through a content analysis. Tornado hazard messaging, due to tornadoes' short-term threat and overarching potential for damage (Ripberger, Jenkins-Smith, Silva, Carlson, & Henderson, 2014), provides an opportunity to study uncertainty language during short-term hazardous scenarios. Across a five-day period, there were N = 2,459 severe weather forecast tweets from 146 Twitter users located in Alabama, Mississippi, Tennessee, and Georgia. Results indicate there were significant relationships between the source of a forecast (i.e., weather media, weather government, and non-weather government) and uncertainty expression. Weather media sources were significantly less likely than government sources (both weather and non-weather) to use uncertainty expressions in their forecast tweets. The state the Twitter source was located also influenced the amount of uncertainty expressed within a forecast. For example, tweets from areas with a greater number of tornadoes were significantly less likely to contain uncertainty expressions than were areas with fewer threats. Also, time (measured as the number of days before tornado touchdown) was shown to have a significant relationship with uncertainty expression, as the amount of uncertainty expressed decreased the closer in time the messages were to the tornadic event. Due to the large amount of uncertainty in weather prediction, meteorological forecasts during severe events provide a unique, fascinating area for future research on risk communication and public safety messaging.